Controllable graphene coated mesoporous carbon/sulfur composite for lithium–sulfur batteries1. Issue 90 (2nd October 2015) - Chen, Shanliang; Tang, Qunli; Chen, Xiaohua; Hu, Aiping; Deng, Weina; Liu, Zheng
<x xml:space="preserve">Abstract</x> We present the construction of a CMK-3/S composite which is controllably coated with graphene via the functionalization of the CMK-3 surface with the assistance of a bridging agent (l-lysine and PEG).